1993 World Economic and Financial Surveys : International Capital Markets; Part II. (World Economic and Financial Surveys; World Economic and Financial Surveys ;, 1993)
This paper discusses systematic issues in international finance explained in the International Capital Markets report. The paper describes that the nature and extent of recent banking problems in several industrial countries along with the policy responses to those problems. It is observed that balance sheet problems in banking are widespread among the major industrial countries. The paper also analyses recent activity in the European currency unit bond and exchange markets, and reviews developments in the private financing of developing countries and discusses several issues raised by the recent experience, including the broadening of the investor base for developing country securities, the special role played by regional financial centers in East and Southeast Asia, and the systemic implications of the evolving pattern of developing country financing. A key influence on international capital movements in recent years was the rising international diversification of investment portfolios, which is generally believed to have increased in response to the liberalization of exchange and capital controls in many industrial countries in the 1970s and 1980s.